The information age (or digital age) and the integration of archives, libraries and museums:: realities in Brazil and the United States of America - Miranda, Zeny Duarte de (Revista Fontes Documentais, 2023)
Deals with the reach of Archival Science, Librarianship and Museology to the status of sciences have expanded from the understanding of the university academy about the role of these areas in the sociocultural, scientific, technological space and, even more, by the evolution of the information age (or digital age). ), one of the most representative brands of the 21st century. Problems today are essentially linked to difficulties in understanding the digital phenomena that occur and are repeated in scientific and philosophical readings that signal the debates about the integration of the aforementioned areas and the advancement of systems in the era of digital humanities. Experiences of institutions/information units in Brazil and the United States of America with interrelated information systems are presented.